STUDY PENGEREMEN PADA MOBIL LISTRIK HASIL MODIFIKASI - A.A. Alit Triadi; Achmad Zainuri; I Made Suartika; I Made Adi Sayoga; I Made Mara; I Dewa Ketut Okariawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Mataram, 2024)
Every three accidents occur every hour in Indonesia, according to the Director of Road Traffic at the Ministry of Land Transportation, with a percentage of over 50-70 percent and 30 percent of accidents occur due to poor performance of the brake system. Accidents occur due to insufficient braking distance and lack of understanding of the braking characteristics of the vehicle being driven. The aim of this research is to analyze the distance, time and braking force required for an electric car to move until it stops with variations in speed and vehicle load. This research was carried out using an experimental method where a prototype electric car was run by varying the speed and load of the vehicle to obtain braking time and distance and analyzing the data obtained. The shortest braking distance at a speed of 20 km/hour with a vehicle load of 950 kg is 4.39 meters. The longest braking distance is 14.78 meters at a speed of 40 km/hour with a vehicle load of 1050kg. The fastest braking time is at a speed of 20 km/hour with a vehicle load of 950 kg, namely 1.97 seconds. The longest braking time was at a speed of 40 km/h with a vehicle load of 1050 kg, namely 2.76 seconds. The smallest braking force is at a speed of 20 km/hour with a vehicle load of 1050 kg, namely 2098.36 N. The largest braking force is at a speed of 40 km/hour with a vehicle load of 950 kg, namely 4132.65 N.